The Moderating Role of Firm Size in the Effects of Operational Risk and Digital Transformation on Financial Performance - Irawan, Andi; Galih Akbar P.R., Ibrahim; Marhamah Zulfa Hiz, Neng Eem; Nugroho, Tri Bayu; Arafah, Willy (Journal of Economics and Business UBS, 2026)
The financial performance of firms in the Indonesian non-cyclical consumer sector is increasingly influenced by operational risk management and digital transformation, while firm size may shape how these factors translate into performance outcomes. This study employed a quantitative approach using panel data regression on non-cyclical consumer companies listed on the Indonesia Stock Exchange during 2019–2024, with purposive sampling and firm size as a moderating variable, analyzed using EViews and fixed effect model selection. Results show that operational risk has a significant negative effect on financial performance, and digital transformation also negatively affects performance, while firm size strengthens the relationship between both variables and financial performance, with an adjusted R-squared of 0.752 indicating strong explanatory power. This study concludes that integrating operational risk, digital transformation, and firm size provides a comprehensive model for explaining financial performance in Indonesian consumer non-cyclical firms, offering implications for managerial decision-making and corporate strategy development. These findings highlight the importance of strengthening risk governance and accelerating digital adoption in medium and large firms, particularly in emerging markets, where resource differences influence the effectiveness of transformation strategies and financial resilience across industries over time. Policy and managerial recommendations should focus on sustainable digital risk integration strategies.